ANALISIS YURIDIS CACAT HUKUM KEPUTUSAN TATA USAHA NEGARA (KTUN) DALAM PUTUSAN PTUN JAYAPURA : NO. 40/G/2018/PTUN.JPR - Adelia hartanti; Aliya azzahra; Dinda trisya; Madinar Madinar; nana ervina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
the Jayapura Administrative Court Decision Number 40/G/2018/PTUN.JPR and their implications for legal protection of the plaintiff. The research method used is normative legal research with statutory and case approaches. The legal materials consist of primary, secondary, and tertiary legal materials analyzed qualitatively. The results of the study indicate that the KTUN in the Jayapura Administrative Court Decision Number 40/G/2018/PTUN.JPR contains legal defects in the form of substantive and procedural defects. The substantive defect is reflected in the absence of a clear legal basis and evidence regarding the determination of payment obligations imposed on the plaintiff. In addition, the defendant could not provide official documents forming the basis for issuing the decision. The procedural defect is reflected in the failure to apply the principles of transparency and accuracy in the issuance process of the KTUN. The KTUN also contradicts Article 53 paragraph (2) of Law Number 9 of 2004 and the general principles of good governance, particularly the principles of legal certainty, accuracy, and transparency. The implications of these legal defects caused material and immaterial losses to the plaintiff in the form of unclear payment obligations and legal uncertainty. Legal protection for the plaintiff was provided through a lawsuit mechanism in the Administrative Court, resulting in the cancellation of the KTUN by the panel of judges.